RESEARCH ASYNCHRONOUS ELECTRIC WITH MICROPROCESSOR CONTROL SYSTEM - and; and (Municipal economy of cities. Series: «Economy science», 2013)
We consider the structure and design of a special booth for research asynchronous electric drive with microprocessor control system at start-up and braking modes. The feature of the stand is the ability to change modes and parameters of the regulator using a personal computer.